2012
DOI: 10.1097/ajp.0b013e318243e2d1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Physical Activity on Pain Thresholds in Patients With Depression and Multiple Somatoform Symptoms

Abstract: Short low-graded exercise can have reducing effects on perception of pressure pain. Physical activity level is a relevant covariate when using pressure pain assessment. Reduced general fitness can partially account for lower pain thresholds in depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 76 publications
0
5
0
1
Order By: Relevance
“…Thirteen studies were excluded after reading the full‐text versions. Reasons for exclusion were: intention to measure delayed onset muscle soreness (exercise‐induced hyperalgesia) instead of EIH, 35,36 not including psychosocial factors in the analysis, 37 not using an exercise bout in the protocol, 38,39 exercise was combined with consuming caffeine, 40 pain intensity was not remeasured after an exercise bout, 41 pain was remeasured after weekly exercise activity, 42 changes in psychosocial factor after exercise were measured, 43,44 pain was measured during exercise, 45,46 and 1 study was a dissertation 47 . Two more studies were included after reading relevant articles and cross‐checking the reference lists 21,48 .…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies were excluded after reading the full‐text versions. Reasons for exclusion were: intention to measure delayed onset muscle soreness (exercise‐induced hyperalgesia) instead of EIH, 35,36 not including psychosocial factors in the analysis, 37 not using an exercise bout in the protocol, 38,39 exercise was combined with consuming caffeine, 40 pain intensity was not remeasured after an exercise bout, 41 pain was remeasured after weekly exercise activity, 42 changes in psychosocial factor after exercise were measured, 43,44 pain was measured during exercise, 45,46 and 1 study was a dissertation 47 . Two more studies were included after reading relevant articles and cross‐checking the reference lists 21,48 .…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon may have been caused by long-term pain experienced by patients with CLBP; this condition indicated that the central nervous and peripheral sensory systems underwent adaptive changes [45,46]. Hennings A [47] studied the effect of physical activity on the pain areas of patients with multiple physical symptoms and found that short-term low-intensity exercise could increase PPT and reduce pain. Moreover, the level of physical activity is a related covariate.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise as therapy has been described for at least twenty types of diseases l i k e Tr p t i ( a n o r e x i a n e r v o s a ) , A p a k t i (indigestion), Gurugatrata (heaviness of the body) and other psychosomatic disorders. Shortlow graded exercise has been shown to decrease pain perception and persons with better fitness show higher pain threshold (29). Decreased pain threshold has been implicated in a number of psychosomatic disorders; hence regular exercise can be one of effective treatment strategies for dealing with somatic pain symptoms.…”
Section: Relavance Of Indian Traditional Medical Knowledge In Treatmementioning
confidence: 99%